Fluid of fused spheres as a model for protein solution - Kastelic, M.; Kalyuzhnyi, Yu.V.; Vlachy, V. (Condensed Matter Physics, 2016)
In this work we examine thermodynamics of fluid with "molecules" represented by two fused hard spheres, decorated by the attractive square-well sites. Interactions between these sites are of short-range and cause association between the fused-sphere particles. The model can be used to study the non-spherical (or dimerized) proteins in solution. Thermodynamic quantities of the system are calculated using a modification of Wertheim's thermodynamic perturbation theory and the results compared with new Monte Carlo simulations under isobaric-isothermal conditions. In particular, we are interested in the liquid-liquid phase separation in such systems. The model fluid serves to evaluate the effect of the shape of the molecules, changing from spherical to more elongated (two fused spheres) ones. The results indicate that the effect of the non-spherical shape is to reduce the critical density and temperature. This finding is consistent with experimental observations for the antibodies of non-spherical shape. В цiй роботi ми дослiджуємо термодинамiку плину з “молекулами”, представленими двома спаяними
твердими сферами, якi декорованi вузлами з притягувальними потенцiалами типу квадратної ями. Взаємодiя мiж цими вузлами є короткодiюча i спричиняє асоцiацiю мiж частинками спаяних сфер. Модель
може бути використана для дослiдження несферичних (чи димеризованих) протеїнiв у розчинi. Термодинамiчнi величини системи розраховуються за допомогою модифiкацiї термодинамiчної теорiї збурень
Вертгайма, i результати порiвнюються з новими симуляцiями методом Монте Карло при iзобаричноiзотермiчних умовах. Зокрема, нас цiкавить фазове розшарування рiдина-рiдина в таких системах. Модельний плин використовується для оцiнки ефекту форми молекул, що змiнюється вiд сферичної до
бiльш видовженої (двi спаянi сфери). Результати вказують, що ефект несферичної форми має зменшувати критичну густину i температуру. Це узгоджується з експериментальними спостереженнями для антитiл
iз несферичною формою.